2019
DOI: 10.3390/su11041122
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Driving Forces of Green Growth: Empirical Analysis on China’s Iron and Steel Industry

Abstract: Green growth of sectors with extensive energy and environmental impacts represented by the iron and steel (IS) industry plays a critical role in fostering sustainable and inclusive development. This paper constructs an updated evaluation model for green growth estimation by combining a global Malmquist–Luenberger index and an epsilon-based measure. A comprehensive decomposition framework is further posited to reveal underlying determinants of green growth. Research findings based on empirical tests from the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Moreover, there are few studies in the available scientific literature on this economic sector in this field. Most often these are studies based on companies operating on Asian markets [5,6,11,60,61], which makes comparison difficult because the European metal production sector has one of the most stringent legal regulation systems, e.g., in the field of environmental protection, while Asian markets do not have such restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are few studies in the available scientific literature on this economic sector in this field. Most often these are studies based on companies operating on Asian markets [5,6,11,60,61], which makes comparison difficult because the European metal production sector has one of the most stringent legal regulation systems, e.g., in the field of environmental protection, while Asian markets do not have such restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Yi and Liu (2015) analyzed the growth situation of the green economy of China by considering variables like population changes and education level… Li and Xu (2018) confirmed that the abundance of resources in one region positively influences environmental degradation. Qin et al (2019) and Wu and al. (2019), respectively, paid attention to the role of iron and steel industries and the electricity substitution policy effect while considering the determinants of green economic growth in China's case.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The green development index has been applied for listed companies [31], manufacturing industries [32,33], or the regional industrial economy [34] in the literature, considering the waste gas, water, and residual emissions by the slack-based measure (SBM) or the Data Envelopment Analysis (DEA) model. The profitability and environmental management indicators of enterprises are also taken into account through regression, panel data, and other econometrics analysis methods [35,36].…”
Section: Literature Reviewmentioning
confidence: 99%